Development of Cocoa Superior Products Through Upstream–Downstream Training in Bodag Village, Kare District, Madiun - Wardani, Ratna Mustika; Budi, Luluk Sulistiyo; Rohcahyani, Fadilla Eka; Choirum Rindah Istiqaroh; Rhavida Anniza Andyani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Bodag Village in Kare District, Madiun Regency, has an agroecological environment that strongly supports cocoa cultivation, with approximately 40 hectares of farmland managed by the Murah Sandang Farmer Group and strengthened by downstream initiatives through the Bodag Chocolate House. However, this potential has not yet translated into optimal productivity, as farmers face several constraints, including limited availability of organic fertilisers, rising production costs due to higher chemical fertiliser prices, and insufficient understanding of sustainable cultivation practices and the utilisation of organic waste. To address these challenges, this community service program implemented a participatory training on the production and application of Liquid Organic Fertilizer (POC) using locally available materials as a more environmentally friendly and economical alternative. The training included socialization, hands-on POC production, technology application in demonstration plots, and evaluation of program effectiveness. The results showed a significant improvement in participants’ knowledge, indicated by an increase in the number of participants in the “understand” and “highly understand” categories and the disappearance of the “do not understand” category. Participants’ enthusiasm also increased in each training session, and the farmer group successfully produced high-quality liquid and solid organic fertilizers. The program's outcomes demonstrate that the training effectively enhanced farmers’ technical capacity, improved their understanding of sustainable cultivation through organic fertiliser production, and strengthened the sustainability of cocoa farming as Bodag Village’s leading commodity. Contribution to Sustainable Development Goals (SDGs):SDG 2 (Zero Hunger)SDG 4 (Quality Education)SDG 12 (Responsible Consumption and Production)SDG 15 (Life on Land)